Viscoplastic behavior of a porous polycrystal with similar pore and grain sizes: Application to nuclear MOX fuel materials. (1st February 2022) - Portelette, Luc; Vincent, Pierre-Guy; Moulinec, Hervé; Gărăjeu, Mihail
Abstract: This study deals with the viscoplastic behavior of a porous polycrystal with pores and grains of similar sizes. Such a microstructure can be encountered in irradiated nuclear Mixed OXide (MOX) fuel materials. MIcronized MASter blend (MIMAS) MOX are multi-phase materials mainly composed of two or three phases depending on their fabrication process. One of these phases corresponds to plutonium-rich agglomerates which strongly evolve during irradiation. The large Pu-rich agglomerates become highly porous due to the accumulation of fission gases and to the apparition of irradiation bubbles. In a past study, Wojtacki et al. (2020) showed that pores distributed inside the Pu-rich clusters have a strong impact on the overall viscoplastic behavior of MOX fuel, when considering a purely isotropic behavior for the Pu-rich clusters. In the present study, the impact of pores similar in size to the surrounding anisotropic grains on the overall viscoplastic behavior is studied in details through numerical full-field simulations. A crystal plasticity model recently developed by Portelette et al. (2018) is used to describe the anisotropic behavior of the polycrystalline matrix with dislocation glide mechanisms. Three-dimensional full-field simulations are performed by a method based on Fast Fourier Transforms (FFT) to compare the behavior of porous materials with that of dense materials. These simulations show that, in the case of spherical pores, their relative size with respect to that of the grains plays a minor role in the overall viscoplastic behavior. However, in the case of polyhedral pores, the relative size effect is more pronounced. With fixed porosity, decreasing the relative size of the cavities with respect to the size of grains leads to a softening of the material and a decrease of the viscoplastic flow stress. Highlights: Viscoplastic behavior of porous polycrystals is obtained by numerical simulations. Full-field calculations are performed using a FFT-based homogenization method. Generated microstructures contain spherical or polyhedral voids. Voids and grains of the porous polycrystals have similar sizes. The relative size effect is more pronounced in case of polyhedral pores.